Upaya Memikat Generasi Muda Bekerja Pada Sektor Pertanian di Daerah Istimewa Yogyakarta - Agus Dwi Nugroho; Lestari Rahayu Waluyati; jamhari jamhari (Universitas Medan Area, 2018)
The purposes of this study was to identify the condition of agricultural labor; know the causes, impacts and strategies to reduce the shift of the youth labor from agricultural to non-agricultural sector. This research was conducted in Bantul, Gunungkidul, Kulon Progo and Sleman regency in 2015. The results showed that the number of households and agricultural enterprises in DIY decrease. The participation of youth in agricultural sector had been decline and the age of agricultural labor DIY was dominated by the farmers over 60 years. Factors which push the shift of the youth from agricultural to non-agricultural was the bigger income on non-agricultural sector, negative image of agriculture, increase of education, narrow land ownership and ease of rural accessibility. While the factors of pull the youth was financial, parental inheritance and government incentives. The impacts of this condition was decrease of the effectiveness and efficiency of agriculture; the scarcity of agricultural labor and increase of the wage. To overcome this, it is necessary to increase the role of youth in the farmers' institutions; introduction of agriculture through early childhood education; improve the quality of agricultural actors; develope integrated agriculture; strengthen cooperative farming; agricultural insurance and marketing guarantees.